1998
DOI: 10.1073/pnas.95.9.4912
|View full text |Cite
|
Sign up to set email alerts
|

The Rhizobium meliloti ExoK and ExsH glycanases specifically depolymerize nascent succinoglycan chains

Abstract: The Rhizobium meliloti ExoK and ExsH glycanases have been proposed to contribute to production of low molecular weight (LMW) succinoglycan by depolymerizing high molecular weight succinoglycan chains in R. meliloti cultures. We expressed and purified ExoK and ExsH and determined that neither enzyme can extensively cleave succinoglycan prepared from R. meliloti cultures, although neutral͞ heat treatment and acid͞heat treatment convert succinoglycan to forms that can be cleaved efficiently by both enzymes. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…This depressed activity may be a consequence of the incompatibility between the intrinsically compact structure of long polysaccharides and the requirement to bind in a thermodynamically disfavored extended conformation across an active site groove. The existence of polysaccharide aggregates has been previously suggested to result in low hydrolysis for the endo-acting GHs ExoK and ExsH from Rhizobium meliloti and BcsZ (16,66). In support of this hypothesis, BcsZ was more efficient at hydrolyzing in vitro synthesized cellulose in situ (67).…”
Section: Figure 7 Pslg Is Not Required For Psl Biosynthesis and Biofsupporting
confidence: 73%
See 1 more Smart Citation
“…This depressed activity may be a consequence of the incompatibility between the intrinsically compact structure of long polysaccharides and the requirement to bind in a thermodynamically disfavored extended conformation across an active site groove. The existence of polysaccharide aggregates has been previously suggested to result in low hydrolysis for the endo-acting GHs ExoK and ExsH from Rhizobium meliloti and BcsZ (16,66). In support of this hypothesis, BcsZ was more efficient at hydrolyzing in vitro synthesized cellulose in situ (67).…”
Section: Figure 7 Pslg Is Not Required For Psl Biosynthesis and Biofsupporting
confidence: 73%
“…An obvious candidate for the production of cell-free low molecular weight Psl is the hydrolysis of the high molecular weight Psl by the action of PslG. Such a mechanism would be similar to the biosynthesis of the low molecular weight succinoglycan, which occurs via the hydrolysis of the high molecular weight polysaccharide by the non-essential extracellular endoglycases (GH16) ExoK and ExsH (66). This low molecular weight form is beneficial but not absolutely required for this rhizobial species to establish symbiosis with its host plants (75,76) and serves as a signaling molecule to facilitate root nodulation and bacterial update into these nodules (76).…”
Section: Figure 7 Pslg Is Not Required For Psl Biosynthesis and Biofmentioning
confidence: 99%
“…essary for the depolymerization of succinoglycan, as well as the endo-1,3-1,4-␤-glycanase, exoK (32,(74)(75)(76). Expression of exsH, the other endoglycanase responsible for LMW succinoglycan production, appears to be maximally expressed in an intact ExpR/Sin quorum-sensing system in mid-logarithmic and early stationary phase.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work with R. meliloti is pertinent to this point. The mature succinoglycan of R. meliloti is not cleaved by the secreted glycanases ExoK and ExsH (52). It was recently demonstrated that the levels of succinylation and acetylation strongly influence the susceptibility of nascent succinoglycan to glycanases (51).…”
Section: Discussionmentioning
confidence: 99%
“…A type I secretion system (encoded by the prsDE genes) is required for the secretion of the EPS-cleaving enzymes ExoK and ExsH (50), and PlyA and PlyB of R. leguminosarum are secreted similarly (14,15). The mature EPS of R. meliloti is not cleaved by the ExoK and ExsH glycanases; these enzymes cleave nascent EPS chains (52), and the absence of the succinyl group decreased the susceptibility of succinoglycan to cleavage (51). It is not known if modification of the R. leguminosarum EPS confers resistance to cleavage by PlyA and/or PlyB.…”
mentioning
confidence: 99%